The woman in the violence : gender, poverty, and resistance in Peru - Alcalde, M. Cristina (Vanderbilt University Press, 2010)
The Woman in the Violence draws on fieldwork conducted in Lima, Peru, one of the largest cities in Latin America, and the life stories of dozens of women to examine multiple forms of violence and how it interrelates in their lives. Gender-based violence continues to blight the landscape of South American urban centers, and this book unravels the personal experiences of those impacted. Alcalde explores the everyday lives of these women before, during, and after an abusive relationship to explore the impact of, and response to, structural, institutional, and interpersonal violence. Focusing on the experiences of women who are predominantly poor, nonwhite, rural-to-urban migrants with little or no formal education, The Woman in the Violence addresses a range of serious concerns. What types of violence do women experience at different stages in their lives? Which identities and roles are manifested throughout their lives, and do some of these increase their vulnerability to different forms of violence? What strategies do women employ to gain some power and control in these situations, and how can we conceptualize these strategies? In examining these questions, The Woman in the Violence contributes to our understanding of violence, gender, race, resistance, and urbanism as it exposes and analyzes systemic violence against women. The everyday forms of resistance these women employ provide significant insight for students, scholars, and health professionals.